Correction: Saber et al. BD-AcAc2 Mitigates Chronic Colitis in Rats: A Promising Multi-Pronged Approach Modulating Inflammasome Activity, Autophagy, and Pyroptosis. Pharmaceuticals 2023, 16, 953 - Sameh Saber; Mohannad Mohammad S. Alamri; Jaber Alfaifi; Lobna A. Saleh; Sameh Abdel-Ghany; Adel Mohamed Aboregela; Alshaimaa A. Farrag; Abdulrahman H. Almaeen; Masoud I. E. Adam; AbdulElah Al Jarallah AlQahtani; Ali M. S. Eleragi; Mustafa Ahmed Abdel-Reheim; et al. (Pharmaceuticals)
Text Correction [...]